Amnion rupture sequence with 'exencephaly': MR findings in a surviving infant. - Ferris, N J; Tien, R D (American Journal of Neuroradiology, 1994)
300 Multiple ChoicesThis is a pdf-only article and there is no markup to show you.full-text.pdf